Penanganan Tindak Pidana di Bidang Perikanan berdasarkan Peraturan Perundang-Undangan di Indonesia - Yuli Winiari Wahyuningtiyas (JURNAL RECHTENS, 2017)
Under the regulations of Law No.31 of 2004 JO Act 45 of 2009 on Fisheries. Indonesia is an archipelago of Indonesia's fishery potentials spread almost throughout the region of sea waters, such as the archipelago, the waters of the territorial sea and the exclusive economic zone of the sea periran. However, the management still many frauds committed by persons who are not responsible. In Indonesia alone, especially in the field of fisheries is still a lot of colored lawlessness done in various ways, the use of fishing gear that is not environmentally friendly, transhipment, and violations of fishing ground. Weak law enforcement criminal acts in the field of fisheries, among others because of the lack of adequate legal tools and institutional support is good, the various problems faced among other limitations of Human Resources who have an understanding of cases of criminal acts in the field of fisheries. Court fishery authority to examine, hear and decide the Crime in the field of fisheries., Tribunal  fishery is  intended  to  ensure the implementation  fish  resources  optimally and provide clarity and legal certainty in law enforcement against criminal acts in the field of fisheries and is expected to provide recommendations policies to implement the rules and refine the rules of court fisheries.